Comparing Islamic and international laws of war: orthodoxy, “heresy,” and secularization in the category of civilians - Salaymeh, L (Oxford University Press, 2021)
This Article investigates how contemporary laws of war rationalize civilian deaths. I concentrate on two specific legal constructions in warfare: the definition of civilian/combatant and the principle of distinction. (The categories of civilian and combatant should be understood as dialogically constitutive and not entirely distinct. In addition, the category of “civilian” is a modern one and premodern legal sources often do not use one term to refer to noncombatants.) I focus on two significant parties in contemporary warfare: al-Qāʿidah (aka Al-Qaeda) and the U.S. military. Al-Qāʿidah diverges from orthodox Islamic law on these two legal issues, while remaining within the Islamic legal tradition. To scrutinize the nature of this divergence, I compare al-Qāʿidah’s legal reasoning to the legal reasoning of the U.S. military. I demonstrate that the U.S. military diverges from orthodox international law in ways that parallel how al-Qāʿidah diverges from orthodox Islamic law. Specifically, both the U.S. military and al-Qāʿidah elide orthodox categories of civilians and expand the category of combatant, primarily by rendering civilians as probable combatants. Based on this comparative analysis, I argue that the legal reasoning of al-Qāʿidah (and other militant Islamist groups) is as secular as it is Islamic; I call this fusion secularislamized law.